Pengaruh Keselamatan dan Kesehatan Kerja Terhadap Kinerja Pegawai pada Dinas Pemadam Kebakaran Kota Bima - Stefanus Freinademetz Landi; Jaenab; Ikbal Irawan (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This research is motivated by several problems found, namely  there are still employees who do not pay attention to occupational safety and health, there are still employees who have not received enough training, which can have an impact on performance. This study aims to find out whether there is a significant influence of occupational safety and health on employee performance at the Bima City Fire Service. This research is included in the category of Population Associative Research in this study using all employees at the Bima City Fire Service which amounted to 56 employees. This study uses a purposive sampling  technique to determine the special characteristics of the research objectives with the sample used being 31 ASN employees from the Bima City Fire Service.The results of the study convey that Occupational Safety and Health have a significant effect on the performance of employees at the Bima City Fire Service.